Designing an Optimal Route Network for the Synchronized Trans Gadjah Mada Electric Bus (TGMEB) using Max-Plus Algebra - Franciscus Budi Pranatta; Marcellinus Andy Rudhito; Dewa Putu Wiadnyana Putra (UIN Sumatera Utara, 2025)
We develop an optimal route network and synchronized timetable for the Trans Gadjah Mada Electric Bus (TGMEB), designed to cover the entire campus with 4 buses and 28 stops. Using literature review, field observation, and online mapping, we create three network candidates-one-, two-, and three-terminal-and model each as a max-plus linear discrete-event system. Service period and periodic departures are derived from eigenvalue-eigenvector analysis and implemented in Scilab 5.5.2 with a max-plus toolbox. The two-terminal layout performs best: its average inter-stop travel time is 32% faster than the other alternatives while keeping departures synchronized and coverage intact. The results confirm that jointly selecting the network architecture and its timetable yields superior campus operations. This is the first campus-scale study that co-designs a multi-terminal electric-bus route network and synchronized timetable via max-plus algebra, optimizing departure throughput and average inter-stop travel time. Unfortunately, this design has not been tested on the field.